Congenital uterine anomalies and perinatal outcomes: a retrospective single-center cohort study - Elisa Zambrotta; Luisa Maria Di Gregorio; Federica Di Guardo; Roberta Agliozzo; Giuliana Chiara Maugeri; Ferdinando Antonio Gulino; Silvia Cutello; Maria Cecilia Cerana; Marco Palumbo (Clinical and Experimental Obstetrics & Gynecology)
Congenital uterine anomalies result from the abnormal differentiation, migration, fusion and canalization of Mullerian ducts with a prevalence of 1-10% for unselected population, 2-8% for infertile women and 5-30% for women with a history of miscarriage. Uterine anomalies are implicated as cause of reduced fertility as well as early pregnancy loss. Moreover, their presence is related to an increased risk of preterm birth, abnormal fetal presentation, cesarean delivery, placental abruption and small-for-gestational age infants. The presented study aims to evaluate the correlation between congenital uterine anomalies and poor perinatal outcomes. This was a retrospective, single-center cohort study including 29 women with congenital uterine anomalies. The control group included 100 women hospitalized for delivery with normal uterine morphology. Primary perinatal outcome was preterm birth (delivery before the 37th week of gestation); secondary endpoints were fetus small for gestational age (SGA) (< 10th percentile weight) and fetal abnormal presentation (non-cephalic presentation at the end of pregnancy). Data are presented as median or frequency. Correlations were compared using Mann-Whitney or Pearson’s chi square test. Statistical tests were considered significant if P < 0.05. Preterm birth, fetal abnormal presentation, small for gestational age fetuses were significantly higher (P < 0.001) in the congenital uterine malformations group. Congenital uterine anomalies are associated with poor perinatal outcomes; moreover, our study shows that type of malformations mostly associated with worse reproductive outcomes are the septate uterus and sub-septate uterus.